Acceptability of a high-protein Mediterranean-style diet and resistance exercise protocol for cardiac rehabilitation patients: Involving service users in intervention design using a mixed-methods participatory approach - Kirwan, Richard; Newson, Lisa; McCullough, Deaglan; Butler, Tom; Davies, Ian G.; Perez de Heredia, Fatima (Frontiers in Nutrition, 2023)
Background: Current cardiac rehabilitation (CR) practices focus on aerobic-style exercise with minimal nutrition advice. This approach may not be optimal for CR patients with reduced muscle mass and elevated fat mass. Higher protein, Mediterranean-style diets combined with resistance exercise (RE) may improve muscle mass and reduce the risk of future cardiovascular events, although such an approach is yet to be trialed in a CR population. Objective: We explored patient perspectives on the proposed design of a feasibility study. Patients reflected on the acceptability of a proposed high-protein Mediterranean-style diet and RE protocol, emphasizing research methodology and the acceptability of the proposed recipes and exercises. Design: We applied quantitative and qualitative (mixed methods) approaches. The quantitative approach involved an online questionnaire (n=40) regarding the proposed study methodology and relevance. A subset of participants (n=12) received proposed recipe guides and were asked to prepare several dishes and complete an online questionnaire regarding their experience. Another subset (n=18) received links to videos of the proposed RE and completed a questionnaire regarding their impressions of them. Finally, semi-structured interviews (n=7) were carried out to explore participants’ impressions of the proposed diet and exercise intervention. Results: Quantitative data indicated a high level of understanding of the intervention protocol and its importance within the context of this research. There was a high degree of willingness to participate in all aspects of the proposed study (>90%). The trialed recipes were enjoyed and found to be easy to make by a majority of participants (79% and 92.1%, respectively). For the proposed exercises 96.5% of responses agreed they would be willing to perform them and, 75.8% of responses agreed they would enjoy them. Qualitative analysis revealed that participants viewed the research proposal, diet and exercise protocol in a positive light. The research materials were considered appropriate and well explained. Participants suggested practical recommendations for improving recipe guides and requested more individual-focused exercise recommendations, and more information on the specific health benefits of the diet and exercise protocols. Conclusions: The study methodology and the specific dietary intervention and exercise protocol were found to be generally acceptable with some suggested refinements.